Public resale of mobile telephone minutes: An alternative access for low-income households in Colombia (2010)
In recent years in Colombia, the informal resale of mobile telephone minutes as an alternative means of access to mobile telephony has allowed access for many low-income people not financially eligible for mobile plans. With data from a 2007 survey of low-income households in Colombia, we analyzed the main factors that determine the use of this kind of service. Using a probabilistic model (Logit), we found that people with a prepayment plan and those from smaller cities are more likely to use this alternative. Also, those subscribers in a plan with the leading carrier tend to use this service more often. © 2010 Elsevier Ltd.